Activity patterns of arboreal mammals that move using power lines in a Neotropical urban ecosystem - Isabela V. Conti; Remington J. Moll; Raul Costa-Pereira (Urban Ecosystems, 2026)
With the suppression of continuous tree canopies in cities, some arboreal mammals resort to using overhead power line networks to navigate urban landscapes. Surprisingly, although sightings of mammals moving on electrical wires are common in tropical and temperate cities, we still know very little about mammal activity patterns on these human-built structures. Importantly, electrocution is a significant cause of death for mammal species that travel along overhead wires and climb onto transformers. Here, we deployed arboreal camera traps to quantify spatial and temporal activity patterns of canopy-dwelling mammals moving on electric wires around one of the largest urban forests in Brazil. Also, we investigated seasonal variation in their temporal activity patterns across the austral dry and rainy seasons. We obtained 9,158 independent records of four species of arboreal or semi-arboreal mammals, with the Black capuchin monkey ( Sapajus nigritus ) accounting for most of the detections, followed by the Paraguayan hairy dwarf porcupine ( Coendou spinosus ). Overall, species-specific activity patterns remained consistent across seasons and aligned with those observed in natural habitats, indicating a convergent diel niche in urban and natural environments. Our results shed new light on the neglected ecology and natural history of mammals that use electric wires to navigate urban spaces, providing insights to attenuate human-wildlife conflicts and to inform the planning of more wildlife-friendly cities.